Microplastics in Organs of Commercial Marine Fishes from Five Fishing Ports in Java Island, Indonesia - Defri Yona; Mangesti Reza Evitantri; Danu Setia Wardana; Dyah Ajeng Pitaloka; Diana Ningrum; Mochamad Arif Zainul Fuas; Yuniar Ponco Prananto; Ledhyane Ika Harlyan; Atsuhiko Isobe (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Microplastics have been found in the marine environment worldwide. Due to their very small size, it could be ingested by marine organisms from small size plankton to big size fish. The aim of this study is to assess the variability of microplastics in three different organs (gills, gastrointestinal tracts, and muscles) of commercial fishes in five different fishing ports in East Java Province, Indonesia. A total of 137 fish samples from 14 species were extracted to identify the types of microplastics. The microplastics found in the fish samples were mostly dominated by fiber, fragments, and a little quantity of film. In most species, the gills accumulated more microplastics compared to the gastrointestinal tracts and muscles. Gill is the organ that is highly exposed to the environmental conditions, therefore, it is more susceptible to the microplastic contamination. The results showed that there was an inverse relationship between the size of the fish and the occurrence of microplastics (P<0.05). Small size Sardinella lemuru contained more microplastics than bigger size fish such as Katsuwonus pelamis. The variability of microplastics found in this study showed important factors such as habitat, fish size, feeding behavior, and organ function which influenced the ingestion process of microplastic. This study also revealed the presence of microplastics were not only in the gills and gastrointestinal tracts of fish, but also in its muscles. Since this study targeted commercial fishes, further research is needed to know the possible impact on human consumption of fish containing microplastics.